Peningkatan Hasil Belajar Siswa pada Pembelajaran Tematik Terpadu dengan Pendekatan Saintifik di Sekolah Dasar - Rahmadany, Muthiya; Mansur, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research was motivated by the low learning outcomes of student in class 1 SDN 05 Puhun Pintu Kabun Bukittinggi City. The purpose of this study was to describe an increase in student learning outcomes in integrated thematic learning with a scientific approach in class 1 SDN 05 Puhun Pintu Kabun Bukittinggi City. The research subjects were researchers (practitioners), teacher (observers) and 20 students. The research location is SDN 05 Puhun Pintu Kabun Bukittinggi City. The results showed an increase in: a) observation of RPP first cycle was 86,10% (B), second cycle 97,22% (SB); b) observation of teacher aspects of first cycle 81,24% (B), second cycle 90,62% (SB); c) observation of student aspect of first cycle  84,38% (B) and second cycle 93,75% (SB); d) students learning outcomes in the first cycle 76.62 (C), and the second cycle 83,91% (B)